2007
DOI: 10.1590/s0074-02762007000300019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fosmidomycin on metabolic and transcript profiles of the methylerythritol phosphate pathway in Plasmodium falciparum

Abstract: Key words: Plasmodium falciparum -malaria -fosmidomycin -isoprenoid biosynthesis -real time polymerase chain reaction Malaria is a leading cause of morbidity and mortality in the tropical regions, with 300 to 500 million clinical cases and 1.5 to 2.7 million deaths per year (Snow et al. 2005). With the availability of the complete genome sequence from Plasmodium falciparum, increasing attention has focused on transcript profiling and proteomic analyses of the parasite stages responsible for severe disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
3
34
0
1
Order By: Relevance
“…Labeling experiments demonstrate that these dolichols are formed from FPP and GPP, respectively (123,124). As expected, dolichol synthesis is also sensitive to fosmidomycin treatment (37 (125). The parasite is sensitive to known inhibitors of GPI synthesis, such as the mannose analogue 2-deoxyglucose (126,127).…”
Section: Dolicholsmentioning
confidence: 54%
See 2 more Smart Citations
“…Labeling experiments demonstrate that these dolichols are formed from FPP and GPP, respectively (123,124). As expected, dolichol synthesis is also sensitive to fosmidomycin treatment (37 (125). The parasite is sensitive to known inhibitors of GPI synthesis, such as the mannose analogue 2-deoxyglucose (126,127).…”
Section: Dolicholsmentioning
confidence: 54%
“…Analysis of MEP pathway intermediates in bacteria and P. falciparum has established that fosmidomycin reduces the intracellular levels of downstream MEP pathway metabolites and isoprenoid products (35)(36)(37). In addition, the growth inhibitory effects of fosmidomycin are chemically rescued in bacteria and malaria parasites through supplementation of the medium with IPP or unphosphorylated isoprenols (farnesol and geranylgeraniol).…”
Section: Fosmidomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…A diminished membrane potential is consistent with the role of the apicoplast isoprenoid pathway in ubiquinone biosynthesis. It has been demonstrated that FOS inhibits ubiquinone biosynthesis (17,32). Ubiquinones participate in the electron transport chain, and their biosynthesis relies on the MEP pathway to provide precursors for the isoprene side chain that anchors them into the inner membrane of the mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that MEP intermediates are present in gametocytes (Table 1) and that isoprenoids are essential for gametocytogenesis, suggesting that the loss of FOS and MMV008138 activity in gametocytes, especially during the early stages (38,48), may be due to lack of transport mechanisms for these inhibitors or unknown metabolic regulation factors. The apicoplast is the sole source of isoprenoid precursors through the MEP pathway during the intraerythrocytic stages, as the human erythrocytes do not have an active mevalonate pathway to synthesize IPP (27,(49)(50)(51). In addition, it is unlikely that IPP can be scavenged from human plasma at the required concentration (200 M) because it has not been detected in the human serum metabolome (52).…”
Section: Discussionmentioning
confidence: 99%